Data collection in support of the Endocrine Disruption (ED) assessment for non‐target vertebrates. Issue 5 (4th May 2020) - Martin, Olwenn; Ermler, Sibylle; McPhie, Joanne; Scholze, Martin; Baynes, Alice
Abstract : To harmonise vertebrate OECD Test Guidelines for endocrine disruption testing between mammalian and non‐mammalian test species, additional Estrogen, Androgen, Thyroid and Steroidogenesis (EATS) modality endpoints in non‐mammalian models need to be assessed. These would mean for example the addition of hormonal measurements in fish, birds and amphibians. Furthermore, a better reporting of gross pathology findings for birds would also be considered advantageous for the assessment of endocrine disrupting properties.To facilitate adoption of additional measures, guidance on how to perform, report and evaluate these new endpoints is required. In this report, a variety of methods including a systematic evidence map, an extensive literature review and a survey of ecotoxicology laboratories were adopted to collect data on the topic. The systematic evidence map uncovered a range of methods for measuring sex and thyroid hormones in fish, birds and amphibians, although methods for measuring sex‐hormones in fish, were by far, the most frequently encountered in the literature and laboratory survey. However, there are still considerable gaps in knowledge for: optimum sample timing for hormonal measurement (diurnal, developmental stage, etc.), issues with inherent variability, low sample volume (plasma/serum), test species selection, possible impacts of housing/diet/stress. The extensive literature review revealed that although gross pathology and histopathology have been used to investigate the effects of endocrine disrupting chemicals in birds, there are no standardised methods for assessment or interpretation, although relative weight of endocrine organs is frequently used as a gross pathology metric. Reports of how histopathology was assessed varied considerably. From the survey, few contract laboratories are experienced in conducting the avian test guideline and these types of pathology techniques.Recommendations for future work with non‐mammalian taxa include: investigating the optimal time (or timings) for measuring hormones, developing non‐invasive hormone measuring techniques, gaining knowledge of baseline/control hormonal data, and further developing guidance on conducting and assessing gross pathology and histopathology in birds.